(3TQM GdThGgO GdcHQis - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s ((3eUQ s)
(3ChdgG (B:s
(3hHYO deG QCjJ TOI EgJeGe eMUdj GdfMh aj GdeOGQc, hZGjI CdaJge HcJGH CdajI GHf eGdc s
(3BNQgG (B:s
(3GdEYQGH(B: (3XGgQ GdETJTgGO ajg aj bhdg GdCLdd hgPG BNQ eG LeYfGg ef GdThGgO GdThGQO hef GdfhGOQ s
(3CdajI GHf eGdc GdeSeGI HGdNdGUIs
(3HYV GdThGgO eTchdIs
(3HgG fXGe GdJYbjHIs
(3HChd cd LRA efgeG agQS ddehVhYGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdfMhs